Y chromosome variation and prostate cancer ancestral disparities - Pamela X.Y. Soh; Alice Adams; M.S. Riana Bornman; Jue Jiang; Phillip D. Stricker; Shingai B.A. Mutambirwa; Weerachai Jaratlerdsiri; Vanessa M. Hayes (iScience)
Summary: Prostate cancer (PCa) is marked by significant ancestral bias, with African men disproportionately impacted. However, genome profiling studies have yet to explore the mutational landscape and disparity contribution of the male-determining Y chromosome. Using a cohort of 106 African and 57 European PCa cases, biased toward aggressive presenting primary disease, we performed complete Y chromosome interrogation for inherited and somatic variance. Capturing unexplored early-diverged Y-haplogroup substructure, while European men are 3.1-fold more likely to present with a rare potentially deleterious germline variant, a higher proportion of African patients acquired Y chromosome tumorigenic events (26.4% African, 14% European). While somatic copy number alterations were universally more common to aggressive tumors, besides shared alterations impacting DDX3Y and USP9Y, African derived tumors were prone to somatic losses associated with KDM5D, PCDH11Y, and RBMY. This much-needed African inclusive study alludes to possible Y chromosome contribution, at least in part, to treatment resistance and worsened mortality rates in African men.